Effect of Combination of Aroma Therapy Lavender and Classical Music Towards a Decrease in Anxiety Levels Moderate and Severe on Third Trimester Pregnant Women - Aisyah, Risqi Dewi; Suparni, S.; Fitriyani, F. (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Anxiety disorders are more common in women than men, ie during the pregnancy period and occur during pregnancy and after childbirth, pregnancy anxiety disorders are associated with the occurrence of preterm birth, low birth weight, and decreased apgar score when the baby is born. The purpose of this study was to determine the effect of a combination of lavender aroma therapy and classical music to overcome anxiety in third trimester pregnant women before and as soon as given a combination of lavender and classical music aromatherapy. The type of research used is a quasy experiment. The sample of this study used Cluster random sampling which is 50 trimester III pregnant women. The data collection used the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire, and before that an ethical test was conducted, the analysis of the study used the T Test.